Motivation of Postgraduate Learners in Pursuing Their Doctoral Degree Through Collaborative Learning - Zulaika Zakariah,; Raemah Abdullah Hashim,; Nuruliannah Musa, (2018)
This paper explored the idea of what motivates part time postgraduate learners to stay engaged in a collective e-learning environment of a private university in Malaysia. Findings indicate that the respondents felt that collaborative learning could cultivate motivation among peers.